Stigma Jurusan Pendidikan : Analisis Sosiologis Terhadap Rendahnya Minat Menjadi Guru - Zhafira Ramadhani; Putri Salma; Fikron Yunus; Abdul Fadhil (Advances In Education Journal, 2026)
The low interest of the younger generation in becoming teachers is one of the challenges in the regeneration of the teaching workforce in Indonesia. This phenomenon is influenced by various factors, including the growing stigma against education majors as a result of social construction in society. This study aims to analyze the stigma against education majors and its influence on the low interest in becoming teachers from the perspective of educational sociology. The study used a library research method with a descriptive qualitative approach. Data were obtained from journals, books, and relevant scientific documents, then analyzed using content analysis. The results show that the stigma against education majors is formed through a process of social construction, reinforced by social interactions, and influenced by economic, sociocultural, family factors, professional prestige, developments, and government policies. Therefore, increasing interest in becoming teachers requires improvements in welfare as well as changes in public perception of the teaching profession.